Unpacking Turkey's security footprint in Africa: Trends and implications for the EU - Nebahat Tanrıverdi Yaşar (Stiftung Wissenschaft und Politik (SWP), 2022)
African states are aspiring to strengthen their defence capabilities against the backdrop of ongoing instability in the continent. Turkey has lately added security and defence cooperation to its existing soft power instruments and laid the foundations for long-term strategic cooperation with African countries. Increasing drone sales are an important part of this cooperation, but they are not its only component. A mutually reinforcing policy design of arms exports, military training, and defence diplomacy allows the Turkish administration to build long-term and institutional bonds with African countries. Today, Turkey is one among many security providers that African states can choose from. Also, the European Union (EU), in its February summit with the African Union, committed to strengthening its role in addressing shared peace and security challenges in the continent. To achieve this goal, the EU and its member states should revisit potential cooperation areas with partners that are active in the continent and consider the benefits of potential cooperation with Ankara.
Keywords: 320